Ticks of new world tapirs - Labruna, M.B. (2009)
In this paper, we present an updated list of ticks that have been found infesting New World tapirs. For this purpose, literature records were obtained from the INTA tick database. Data are presented according to tick species, tapir species, and country. A total of 27 tick species have been reported infesting New World tapirs. Most of the reports were on T. terrestris (20 tick species in 10 countries). Thirteen tick species were reported on T. bairdii in 3 countries, and only 2 tick species on T. pinchaque in 2 countries. Ticks reported on tapirs comprised 18 species of the genus Amblyomma, and 7 other species representing the genera Ixodes, Haemaphysalis, Dermacentor, and Rhipicephalus from the Ixodidae family, and at least 2 Ornithodoros species from the Argasidae family. Indeed, tapirs are very significant hosts for the Neotropical tick fauna. Since tapirs are usually found in less fragmented biomes with high biodiversity, and the richness of tick species is higher in tapirs than any other Neotropical vertebrate species, further studies are needed to evaluate the role of tapir-associated ticks on biodiversity. The role of these ticks on tick-borne diseases for tapir and other vertebrates also needs further investigations.